Research on 5G base station radiation safety and corresponding network planning - Hao XU; Hongyi CAO (Dianxin kexue)
With the rapid development of 5G network, the radiation safety of base stations is a hot issue of public concern.As 5G has the characteristics of high frequency band and large bandwidth, ultra-dense heterogeneous network applications are becoming more common.The impact of electromagnetic radiation from typical 5G base stations on the human body was analyzed, and the safety distances of base stations with different powers were calculated in detail.Based on various common 5G base station equipment forms such as outdoor macro stations, outdoor pole stations, telephone booth base stations, and indoor micro stations, the safe area of different scenarios was analyzed and theoretically calculated.The results were verified based on field test and specific networking planning recommendations were proposed.